AI-Powered Structural and Co-Expression Analysis of Potato (Solanum tuberosum) StABCG25 Transporters Under Drought: A Combined AlphaFold, WGCNA, and MD Approach - Kurt, Baris; Kurt, Firat (Mdpi, 2025)
Drought stress significantly impacts potato (Solanum tuberosum) yield and quality, necessitating the identification of molecular regulators involved in stress response. This study presents a systems-level, integrative in silico strategy to characterize StABCG25 transporter homologs, key players in abscisic acid (ABA) export in Arabidopsis, to evaluate their potential role in drought adaptation. We performed a genome-wide scan of the potato genome and identified four StABCG25 isoforms. A comprehensive computational framework was applied, including transcriptomic profiling, Weighted Gene Co-expression Network Analysis (WGCNA), AlphaFold2-based 3D modeling, docking, and long-timescale Molecular Dynamics (MD) simulations. Expression analyses revealed the coordinated upregulation of StABCG25-2 and -4 in the drought-tolerant FB clone, contrasted by suppression or instability in sensitive cultivars. WGCNA placed StABCG25-2 as a hub gene in ABA-enriched stress response modules, while StABCG25-4 was associated with plastid-related pathways, suggesting functional divergence. Structurally, StABCG25-2 and -6 exhibited high conformational stability in MD simulations, supported by consistent RMSD/RMSF profiles and MM/PBSA-based binding energy estimates. In contrast, StABCG25-5B, despite favorable docking scores, demonstrated poor dynamic stability and unreliable binding affinity. Overall, this study highlights the critical role of transcriptional coordination and structural robustness in the functional specialization of StABCG25 isoforms under drought stress. Our findings underscore the value of combining WGCNA and molecular dynamics simulations to identify structurally and functionally relevant ABA transporters for future crop improvement strategies.
Keywords: Stabcg25 Transporter; Alphafold; Molecular Dynamics Simulation; Wgcna (Weighted Gene Co-Expression Network Analysis); Aba Transport